ILLEGAL CURRENCY TRADING SCHEME: AN EMPIRICAL STUDY FROM ISLAMIC PERSPECTIVE - Muhammud, Farah Safura; Umor, Nur Airin Hafiza (Jurnal 'Ulwan, 2024)
Illegal currency trading schemes are illegal trading schemes that are prohibited in Islam because there are elements that violate Islamic Sharia such as riba, gharar, maysir elements that prevent Muslims from engaging in illegal currency trading such as Forex, Bitcoin etc. This study was carried out in an effort to educate the community, particularly Muslims, about the dangers of illegal currency trade and to encourage them to exercise greater caution when engaging in any activity that involves trading. This research has been done through qualitative analysis which is interview through face-to-face interviews. The researchers have used transcription and content analysis methods to quantify and analyse the existence, meanings, and linkages of certain words, themes, or concepts of the topic. The results of the study have answered the research questions about the concept of illegal currencies trading schemes in islamic perspective, the factors that influence Malaysians and Muslims to involve in illegal currencies, and the last question is about how to prevent the illegal currency traders. The conclusion is various factors that cause people in Malaysia to be affected by these schemes.